2020
DOI: 10.4314/jasem.v24i8.4
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Population Growth on Deforestation in Nigeria: 1991 – 2016

Abstract: This study examines the effects of population growth on deforestation in Nigeria between 1991 and 2016. Anthropogenic factors especially population growth were identified to be the major forces responsible for deforestation in Nigeria. The Augmented Dickey Fuller (ADF) test was used to establish stationarity among the variables and the Johansen cointegration test was used to establish a long run relationship between population growth and deforestation in Nigeria. Population growth was found to have a negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Meanwhile, the direction of the relationship differs from what is documented in many literatures. For example, researchers such as; (Oyetunji et al, 2020;Legese & Roba, 2021;Hussain et al, (2022) indicated that loss of forest cover increases when population growth increases. However, this finding showed annual loss intensity of forest cover increases with a decrease in the annual rate of change in population.…”
Section: Loss Of Forest Landmentioning
confidence: 99%
“…Meanwhile, the direction of the relationship differs from what is documented in many literatures. For example, researchers such as; (Oyetunji et al, 2020;Legese & Roba, 2021;Hussain et al, (2022) indicated that loss of forest cover increases when population growth increases. However, this finding showed annual loss intensity of forest cover increases with a decrease in the annual rate of change in population.…”
Section: Loss Of Forest Landmentioning
confidence: 99%
“…According to this theory, unchecked population growth tends to grow geometrically, putting pressure on a fixed stock of resources, resulting in disasters such as diseases, starvation, and war which eventually lower growth through increased death rates (Malthus 1798). From these concerns, family planning campaigns grew in strength since the 19th century in the hope that rapid population growth would pose a threat because resources would be diverted from capital growth to accommodate the growing population—which is thought to be associated with unemployment, declining income, environmental pollution, deforestation, and disease risks (Asongu 2013; Asongu and Jingwa 2012; Bloom, Canning and Sevilla 2003; Byaro, Mafwolo and Mayaya 2022 ; Oyetunji et al 2020; Preston 1996; Sweezy 1940; Byaro, Mayaya and Pelizzo 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nigeria has one of the highest rates of deforestation of primary forests where more than 50% of such forests have been lost in the past (Mfon et al, 2014;Oyetunji et al, 2020). Several reasons contribute for deforestation in Nigeria and all over the world, according to Bamba et al (2011).…”
Section: Introductionmentioning
confidence: 99%